Dampak Strategi Team Games Tournament (Tgt) Terhadap Hasil Belajar Matematika Siswa Kelas V SD Muhammadiyah 21 Baluwarti Tahun Pelajaran 2016/ 2017 - Ariyanti, Tri Henny, Drs. Suwarno, SH., M.Pd (2017)
The purpose of this study is to describe and analysis about the impact of learning math with the use of strategy towords learning outcomes for mathematics. The subject in the research of the 5th grade students of SD Muhammadiyah 21 Baluwarti Surakarta. Methods of the data comprised is method liliefors to the for normality. The research result obtained average value material fractions math learning outcomes sub themes change the fractions to presents and vice versa as well as change the fractions to decimal form by using conventional learning strategies is lower than the average of the results of the study material maths fractions sub themes change the decimal to pecent and vice versa as well as changing decimal to fractions using the learning strategy Team Games Tournament (TGT) i.e. 57,71 > 81,07. From the results of data analysis with sinifikansi 5 % obtained that there is a defference between the significance of learning strategy Team Games Tournament (TGT) and conventional learning towards the learning outcomes for mathematics. The conclusion this study is there is a positive impact of the Strategy Team Games Tournament (TGT) against the results of the study of mathematics students. Thus, the Strategy Team Games Tournament (TGT) can improve the results of learning math student.